A call to evaluate Plastic's impacts on marine benthic ecosystem interaction networks. (15th March 2021) - Ladewig, Samantha M.; Bianchi, Thomas S.; Coco, Giovanni; Hope, Julie A.; Thrush, Simon F.
Abstract: Plastic pollution continues to seep into natural and pristine habitats. Emerging laboratory-based research has evoked concern regarding plastic's impact on ecosystem structure and function, the essence of the ecosystem services that supports our life, wellbeing, and economy. These impacts have yet to be observed in nature where complex ecosystem interaction networks are enveloped in environmental physical and chemical dynamics. Specifically, there is concern that environmental impacts of plastics reach beyond toxicity and into ecosystem processes such as primary production, respiration, carbon and nutrient cycling, filtration, bioturbation, and bioirrigation. Plastics are popularly regarded as recalcitrant carbon molecules, although they have not been fully assessed as such. We hypothesize that plastics can take on similar roles as natural recalcitrant carbon (i.e., lignin and humic substances) in carbon cycling and associated biogeochemistry. In this paper, we review the current knowledge of the impacts of plastic pollution on marine, benthic ecosystem function. We argue for research advancement through (1) employing field experiments, (2) evaluating ecological network disturbances by plastic, and (3) assessing the role of plastics (i.e., a carbon-based molecule) in carbon cycling at local and global scales.